Visual Effect Of Merchandising Store Atmosphere, Price Discount On Impulse Buying Behavior Of Ramayana Malang Customers - Edi Putra; Aprilian Rufianto; Try Junanto; Ai Suminar (OIKONOMIA: Journal of Economics and Management Science, 2023)
This research aims to analyze the influence of visual merchandising, store atmosphere, price discounts on impulse buying behavior of Ramayana Malang customers. This research was conducted at the Ramayana department store. In addition, these literature review are connected to the aspect of impulsive buying. Therefore, the main purpose of this study is to find out the form of influence given from the visual effect that of merchandising store atmosphere, price discount on impulsive buying behavior of Ramayana Malang customers. The method used in this study is a form of literature study method by applying elements of qualitative methods from various journals. The results of the study show some of the major influences that occur due to impact of impulsive buying behavior which refer to several results, namely; (1) Impact of merchandising store atmosphere on impulsive buying behavior (2) The impact of price discount offer on impulsive buying behavior.